If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -10 = 2x + -34 Reorder the terms: -10 + x = 2x + -34 Reorder the terms: -10 + x = -34 + 2x Solving -10 + x = -34 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -10 + x + -2x = -34 + 2x + -2x Combine like terms: x + -2x = -1x -10 + -1x = -34 + 2x + -2x Combine like terms: 2x + -2x = 0 -10 + -1x = -34 + 0 -10 + -1x = -34 Add '10' to each side of the equation. -10 + 10 + -1x = -34 + 10 Combine like terms: -10 + 10 = 0 0 + -1x = -34 + 10 -1x = -34 + 10 Combine like terms: -34 + 10 = -24 -1x = -24 Divide each side by '-1'. x = 24 Simplifying x = 24
| 4x-9x=13-63 | | 3(5x-6)=42 | | 7x+6=-5x | | 5x+7(x+1)+3=10-6x | | x-.2x=1300 | | 0.16(5x-2)=0.4x+17 | | 122-2x=16x+20 | | w^5x^4y^5-wxy=0 | | 77.50=.15x+10 | | -12a^6+8a^3=0 | | 18x^3-60x^2=-50x | | 12x*x^2=0 | | 6x-8=82 | | 3x+21=63 | | 187-5x=40x+22 | | 16x^2-24x+9=13 | | 12x*1x^2=0 | | 12x*1x^2=x | | 2x*1x^2=0 | | 2x*1x^2=x | | 3x^2+5x-18=0 | | 99-3x=4x | | 10x^2+31x-14=0 | | 4m^2+3m=1 | | b+2.35=9.78+2b+7.22 | | v^2-9v-10=0 | | 4a-12b+20a= | | m^2+9m+18=0 | | 4h^2-4h+1=0 | | e^2-5e-84=0 | | 2(3-7y)=4y+2 | | 6l^2-5l-4=0 |